2010
DOI: 10.1093/schbul/sbq054
|View full text |Cite
|
Sign up to set email alerts
|

Phenomenological Dimensions of Sensory Gating

Abstract: Contemporary sensory gating definitions are generally tied to the perceptual and attentional phenomenology described by McGhie and Chapman, including abnormalities in the quality of sensory input, heightened awareness of background noises, and poor selective attention reported by individuals with schizophrenia. Despite these explicit phenomenological origins, little is known about the experiential phenomena underlying contemporary operationalizations of the sensory gating construct, such as whether the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
73
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 69 publications
5
73
1
1
Order By: Relevance
“…Similar descriptions (Freedman & Chapman, 1973;McGhie & Chapman, 1961) remain largely ignored despite being relatively common and related to stress and fatigue (see also Landon et al, 2012) that on their own have been shown to increase sensitivity to sounds in nonclinical samples (Hasson, Theorell, Bergquist, & Canlon, 2013). These descriptions are consistent with a failure of sensory gating (Hetrick et al, 2012) and feature in many clinical populations (Stansfeld et al, 2000). However, to date little has been done at the clinical level to recognize these difficulties and support improved coping (Landon et al, 2012;Stansfeld et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Similar descriptions (Freedman & Chapman, 1973;McGhie & Chapman, 1961) remain largely ignored despite being relatively common and related to stress and fatigue (see also Landon et al, 2012) that on their own have been shown to increase sensitivity to sounds in nonclinical samples (Hasson, Theorell, Bergquist, & Canlon, 2013). These descriptions are consistent with a failure of sensory gating (Hetrick et al, 2012) and feature in many clinical populations (Stansfeld et al, 2000). However, to date little has been done at the clinical level to recognize these difficulties and support improved coping (Landon et al, 2012;Stansfeld et al, 2000).…”
Section: Discussionmentioning
confidence: 87%
“…The historical focus of schizophrenia diagnostics on first-rank symptoms (Andreasen & Flaum, 1991;Peralta & Cuesta, 1999) has likely contributed to other aspects, including NS, being overlooked (Cutting & Dunne, 1989;Hetrick, Erickson, & Smith, 2012). Stansfeld et al (2000) emphasize the limited research on NS, psychiatric symptoms, and treatment outcome, suggesting research should extend to general well-being and coping strategies of those with mental health conditions who experience NS.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…As proposed in our introductory model, mood, fatigue and stress, exacerbate symptoms of sensory gating. In fact, previous studies have reported heightened incidence of gating impairment during stressor tasks, indexed by both electrophysiological (White and Yee, 1997) and phenomenological (Hetrick et al, 2012) metrics. A compromise between supplementary challenge and deleterious attrition may therefore be the present block-adaptive protocol.…”
Section: Discussionmentioning
confidence: 95%
“…The Sensory Gating Inventory (SGI; Hetrick et al 2012), a self-report measurement, assesses (1) perceptual modulation (e.g., ''My hearing is so sensitive that ordinary sounds become uncomfortable''), (2) over-inclusion (e.g., ''I notice background noises more than other people''), (3) distractibility by sensory stimuli (e.g., ''There are times when I can't concentrate with even the slightest sounds going on''), and (4) fatigue-stress modulation (e.g., ''it seems that sounds are more intense when I'm stressed''). Two studies utilized this questionnaire and reported significantly deviant scores for participants with ADHD on all subscales compared to NCs, with large effect sizes; Cohen's d ranged from 1.26 to 3.28 (Micoulaud-Franchi et al 2015a, b).…”
Section: Self-and Informant Reports (Subjective Measurements)mentioning
confidence: 99%